An entropic model of Gaia. (7th October 2017) - Arthur, R.; Nicholson, A.
Highlights: Connection of Tangled Nature Model to Logistic growth model. New model of species-environment co-evolution. Demonstration of Gaia arising from random mutation and selfish reproduction. Discussion of possible new mechanism for Gaia. Abstract: We modify the Tangled Nature Model of Christensen et. al. (2002) so that the agents affect the carrying capacity. This leads to a model of species-environment co-evolution where the system tends to have a larger carrying capacity with life than without. We discuss the model as an example of an entropic hierarchy and some implications for Gaia theory.